The influence of carbon nanotube on underwater geopolymer paste based on metakaolin and slag - Ziada, Mahmoud; Tanyildizi, Harun; Uysal, Mucteba (Elsevier Sci Ltd, 2024)
Underwater concrete finds application in many underwater structures, such as port facilities, bridge footings, tunnels, and analogous infrastructural elements. In recent years, a growing significance has been attributed to the investigation of sustainable geopolymer studies conducted on land. Hence, the necessity of researching underwater sustainable geopolymer composites emerged. This study produced metakaolin and slag-based geopolymer paste samples containing carbon nanotubes (CNTs) cast and cured in a dry environment, lake water, and seawater. Also, the present work examined the relation between CNTs and metakaolin and slag-based geopolymers in the context of underwater cast and curing. In order to achieve the intended objective, geopolymer samples with CNTs at 0%, 0.05%, 0.15%, and 0.25% ratios poured in under three distinct environments were prepared and subjected to various tests. Subsequently, examinations were conducted to determine the mechanical and microstructural characteristics of the geopolymer samples poured in the three environments. The conducted tests encompassed compressive strength assessment, temperature measurements, pH measurements, and microstructural analyses. Consequently, the compressive strength of the 0.25% CNT geopolymer samples increased by 32.7% and 34.4% compared to the CNT free-geopolymer samples poured in lake water and seawater, respectively. Thus, in this study, underwater geopolymer samples with compressive strengths of 46 MPa and 49.6 MPa were produced in lake water and seawater, respectively.
Keywords: Underwater geopolymer paste; Carbon nanotubes; Seawater; Lake water